Mathematical modeling of the formation of radioactive pollution by out of project accident at nuclear station - Bobovich, Олег Леонидович; Gorbunov, Сергей Валентинович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
To forecast the amount of works on deactivation and possible quantity, composition and category of radioactive pollution the question on scales, character and degree of pollution of locality in the area of nuclear dangerous objects disposal which arises at accidents of nuclear installations with the emission of radioactive substances into atmosphere is very essential.In work the results of calculation of parameters of radiating conditions at accidents at the atomic power station carried out on suggested calculation model are mentioned. Verification of model is checked on the basis of experimental researches in the zone of Chernobyl catastrophe.